2005
DOI: 10.1111/j.1365-2567.2005.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of T cells in abdominal aortic aneurysms

Abstract: , natural killer cells 7Á3 ± 2Á5%, and macrophages 2%. Freshly isolated T cells were in resting (G 1 ) state, with 25% expressing the activationassociated cell surface antigens major histocompatibility complex II and CD25. When stimulated in vitro, a significant proportion entered S and G 2 phase of the cell cycle, up-regulated CD25, and secreted tumour necrosis factor-a, interferon-c, interleukin (IL)-5 and IL-6. Despite patient differences, the composition of the AAA inflammatory infiltrate was remarkably co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 15 publications
5
66
0
Order By: Relevance
“…NPA-PCR/Vb-specific PCR amplification did not reveal any b-chain TCR transcripts (data not shown). These results are in agreement with those of other investigators (7,40,41) who reported the absence of CD45 + cells or T cells from nonaneurysmal aortic tissue. We (35) reported similar results with control epicardial arteries.…”
Section: T Cells Are Infiltrating Aaa Lesionssupporting
confidence: 83%
“…NPA-PCR/Vb-specific PCR amplification did not reveal any b-chain TCR transcripts (data not shown). These results are in agreement with those of other investigators (7,40,41) who reported the absence of CD45 + cells or T cells from nonaneurysmal aortic tissue. We (35) reported similar results with control epicardial arteries.…”
Section: T Cells Are Infiltrating Aaa Lesionssupporting
confidence: 83%
“…We and others have reported that macrophage uptake occurs predominantly in the tunica adventitia in both humans and animal models (27,29,37,40,50,(52)(53)(54)(55)(56), in association with elastic lamellar tears. Initial adventitial recruitment is mediated by the potent chemotactic properties of MCP-1, followed by subsequent medial invasion (3,4,40,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…The predominant cell types within the infiltrate in AAA tissues are CD3 + T cells (more than 50%), including CD4 + T cells and CD8 + T cells [17]. CD8 + T cells have been found, dating as far back as 1999, in AAAs rather than normal aorta.…”
Section: Cd8 + T Cellsmentioning
confidence: 99%
“…Immunohistochemical staining and flow cytometry suggested that elevated numbers of CD3 + cells (include both CD3 + TCRαβ + and CD3 + TCRγδ + cells), localizing in aortic media and adventitia, were present in aneurysm patients [16,17], which may further led to the death of VSMCs [18]. With the evidence that oligoclonal αβ TCR+T cell populations expansion in aneurysmal lesions from AAA patients, AAA is considered as a specific antigen-driven T cell disease [19,20].…”
Section: T Cells In Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation